2014
DOI: 10.1371/journal.pone.0100760
|View full text |Cite
|
Sign up to set email alerts
|

Ectosomes: A New Mechanism for Non-Exosomal Secretion of Tau Protein

Abstract: Tau is a microtubule-associated protein that aggregates in neurodegenerative disorders known as tauopathies. Recently, studies have suggested that Tau may be secreted and play a role in neural network signalling. However, once deregulated, secreted Tau may also participate in the spreading of Tau pathology in hierarchical pathways of neurodegeneration. The mechanisms underlying neuron-to-neuron Tau transfer are still unknown; given the known role of extra-cellular vesicles in cell-to-cell communication, we won… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
205
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(212 citation statements)
references
References 67 publications
(87 reference statements)
7
205
0
Order By: Relevance
“…2J). Ceramide regulates exocytosis Rohrbough et al, 2004) and exosomal secretion (Trajkovic et al, 2008), and tau might be secreted in association with small vesicles such as exosomes and other microvesicles (Dujardin et al, 2014). GW4869, an inhibitor of ceramide generation by neutral sphingomyelinase (nSMase), reduced tauGLuc1/2 reporter secretion from HEK293T cells by 32% (Fig.…”
Section: A Sensitive Live-cell Assay For Monitoring Secretion Of Tau mentioning
confidence: 99%
“…2J). Ceramide regulates exocytosis Rohrbough et al, 2004) and exosomal secretion (Trajkovic et al, 2008), and tau might be secreted in association with small vesicles such as exosomes and other microvesicles (Dujardin et al, 2014). GW4869, an inhibitor of ceramide generation by neutral sphingomyelinase (nSMase), reduced tauGLuc1/2 reporter secretion from HEK293T cells by 32% (Fig.…”
Section: A Sensitive Live-cell Assay For Monitoring Secretion Of Tau mentioning
confidence: 99%
“…Studies also showed differences in propagation (brain areas affected, distance of spreading) after injection of recombinant tau [87,103,104] or native forms [105,107]. Interestingly, tau from human tauopathies brain extracts induced tau pathology mimicking the parent neurodegenerative diseases (Table 2).…”
Section: The Role Of Misfolded Tau In the Seeding And Propagationmentioning
confidence: 99%
“…Tau is constitutively released from neurons under physiological conditions [71,[76][77][78][79][80][81][82][83][84][85][86][87][88]. The secretion is multifaceted, involving diverse intracellular components such as autophagosomes, Golgi, endosomes, ectosomes, lysosomes, microsomes and endoplasmic reticulum [89].…”
Section: Mechanisms Of Tau Release and Spreadingmentioning
confidence: 99%
See 2 more Smart Citations